Upaya Meningkatkan Minat dan Hasil Belajar Siswa Menggunakan Model Kooperatif Tipe Make A Match Pada Mata Pelajaran Quran Hadist Kelas IV di MI Darul Ulum Lemah Putih Wringinanom Gresik - Mahfud, Muhammad (LPPM, 2019)
The effective learning model is a cornerstone of learning practices that make it easy for students to learn and give students knowledge, values ​​and skills. One learning model is the Make a match type cooperative learning model. Make a match gives students the opportunity to ask questions, have opinions and interact with students who are active in class. The teacher acts as a facilitator. Make a match model is a technique to find a partner using a card that contains the answers to these questions. Therefore, learning the Quran hadith makes it easy for students to memorize the meanings and verses of the Holy Qur'an, one of them by the method of Make a match. The focus of this research is on: a) How is the application of the Make a match cooperative learning model? b) What is the student's interest in learning? c) What are the student learning outcomes? and d) What is the response of students ?. This type of research uses Classroom Action Research, a means for researching, perfecting and evaluating the implementation of teacher assignments. The method for initiating this research data, observation sheets, tests and questionnaires. The results of this study indicate that the interests and learning outcomes of students of the Quran hadith subjects in class IV students are said to be still lacking, indicated by the results of observations in class IV students from pre-cycle 61.15%, after the first cycle of 74.07% and the second cycle increased 85.00%. The application of the Make a match type of cooperative learning model for grade IV students at MI Darul Ulum, Wringinom Gresik, was positive because it was seen from the questionnaire percentage of 88%. With this method, student learning outcomes from pre-cycle of 61.15% then increased by 73.9% in the first cycle and held the second cycle increased by 80.5% seen from an increase in each cycle of student learning outcomes has been maximized because it exceeds the target Minimum completeness criteria (KKM). The learning implementation procedure using the Make a match method has been running smoothly and in accordance with the planned learning implementation (RPP).